Impact of intravenous fish oil on omega‐3 fatty acids and their derived lipid metabolites in patients with parenteral nutrition. Issue 2 (21st December 2022) - Weylandt, Karsten H.; Karber, Mirjam; Xiao, Yanan; Zhang, Ingrid W.; Pevny, Sophie; Blüthner, Elisabeth; von Schacky, Clemens; Rothe, Michael; Schunck, Wolf H.; Pape, Ulrich F.
Abstract: Background: Long‐term parenteral nutrition (PN) can lead to intestinal failure–associated liver disease (IFALD). Omega‐3 (n‐3) polyunsaturated fatty acids (PUFAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) were shown to prevent IFALD. EPA‐derived and DHA‐derived oxylipins could contribute to this protective effect. Methods: We analyzed the effect of parenteral fish oil on oxylipins in patients with chronic intestinal failure receiving PN ( n = 8). Patients first received no fish oil for 8 weeks and then switched to PN with 25% of fat as fish oil for another 8 weeks. Fatty acid profiles of red blood cells, PUFA‐derived oxylipins generated by cyclooxygenase, lipoxygenase (LOX), and cytochrome P450 (CYP) pathways, inflammatory markers, and liver function were assessed before and during fish‐oil PN. Results: EPA plus DHA in erythrocytes (the Omega‐3 Index) was high with a median of 11.96% at baseline and decreased to 9.57% without fish oil in PN. Addition of fish oil in PN increased the median Omega‐3‐Index to 12.75%. EPA‐derived and DHA‐derived CYP‐dependent and LOX‐dependent metabolites increased significantly with fish oil in PN, with less pronounced changes in arachidonic acid and its oxylipins. There were no significant changes of inflammation and liver function parameters. Conclusions: This study shows that fish oil–containing PN leads to primarily CYP‐ and LOX‐dependent n‐3 PUFA–derived inflammation‐dampening oxylipins arising from EPA and DHA. Within this short (16‐week) study, there were no significant changes in inflammation and clinical readout parameters.